Golden lettering, Rajesh Mansion - Ayan Ghosh (2023)
Broadway font made from metal in gold polish, the lettering used at Rajesh Mansion. The mansion was formerly called Sorab Mansion and was designed by architect G. B. Mhatre in collaboration with Contractor Kanga & Co.